Problem of Being and Essence in Philosophy of Ibn Sina in Arabic studies - Abd Alsattar Hasan Alsa'ady, Asst. Lect. (lark, 2025)
There is no doubt about the maximally of the concept (existence) to everything perceived,  because every thing and every knowledge it’s contained  by the existence, this is axiomatic . and that what is known apparent or perceptible existence, which match (Existence) in English, but there is another type that is dealt with philosophically is known as true existence, or the existence of being, which match in English (being), this is what we will discuss in this research.    It may be weird for someone to ask about the definition of existence,  It is so clear that it opposes every attempt to clarify it, because it is clearer than everything.  But philosophers have other word;  In their mediation, they deal with the (being) not just with (existence) , as they have attempted to put definitions for it, for multiple reasons, foremost among which are the requirements of metaphysical studies, which depends on defining each concept that is sought to be investigated.    The concept of (essence) linked with (being)  Since Aristotle, this concept has caused a problem in terms of its meaning on the one hand, and in terms of its connection to (being) . From here the problem of existence and essence appeared, and questions were raised such as: How can existence and essence be accurately separated, regardless of the intuition of existence and the intuition of its comprehensiveness?  What is it?  Is there a clear report on Ibn Sina’s position on these two concepts or not?  If there is a difference in his position on understanding the nature of existence and its relationship to essence, why did it happen and how?    On this questions we will put the basis of the research, and we will finish a different result according to a unique reading, Accordingly, we will reach a different result according to a reading different from the usual approach to this problem.
Keywords: Ibn Sina, existence and essence, metaphysics, existence, essence